Peneliltian Tentang Sampah di Kali Lipa Kecamatan Teluk Mutiara Kab Alor tahun 2023 - Dekonius Mau kallang; Melki I. Puling Tang; Anton A. Saetban; Desi Anceria Tuaty; Devi Molina; Dina Maukari; Gadriana Pentele; Ardison Padafing (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the contribution of the government and society in Alor in preventing water pollution in Kali Lipa. Kali Lipa is one of the rivers in Alor which only has a little running water with very dense piles of garbage. The research location is in Lipa, Kalabahi Tengah sub-district, Teluk Mutiara sub-district, Alor district. The data in this study were obtained through field research. Field research was carried out using direct research. The results showed that environmental data to maintain environmental health and social conditions in the field had not been served. In addition, the research results show that the water conditions in the field research contain pollutants. However, the government and the community have not contributed enough to reduce the impact of pollution in the river. In this case, it is necessary to contribute laws and regulations to reduce water pollution.